Bankruptcy problem of the environmentally unfriendly companies in the sustainable regional development - Барбашова, Н. В. (Problems of legality, 2014)
It is shown that existing bankruptcy judgments of the environmentally unfriendly companies do not provide safety for the public and the environment near the object in liquidation. It is proposed to upgrade the regional level of environmental management using the creation of regions with legislative power. Regional authorities must be responsible for the negative impacts associated with the liquidation of the environmentally unfriendly company.